Resolusi Konflik melalui Pendekatan Kearifan Lokal Pela Gandong di Kota Ambon - Hendry Bakri (Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : This paper aims to describe about the conflict in Ambon, Maluku within the period of 1999-2004. Conflict resolution is done in addition to mediation through the Malino agreement, also carried out using local wisdom Pela Gandong which is the bond of two or three more villages that have pledged to work together irrespective of differences in ethnicity, religion and race. Pela Gandong is then cultivate a spirit of reconciliation among the community.Keywords: Conflict Resolutin, Local Wisdom, Pela Gandong, Ambon City